The village world of early medieval Northern Spain : local community and the land market - Portass, Robert, 1983- (Royal Historical Society studies in history. New series., 2017)
In the early eighth century, the Muslim general Tariq ibn Ziyad led his forces across the Straits of Gibraltar and conquered most of the Iberian Peninsula. However, alongside the flourishing kingdom of al-Andalus, the small Christian realm of Asturias-León endured in the northern mountains. This book charts the social, economic and political development of Asturias-León from the Islamic conquest to 1031. Using a forensic comparative method, which examines the abundant charter material from two regions of northern Spain - the Liébana valley in Cantabria, and the Celanova region of southern Galicia - it sheds new light on village society, the workings of government, and the constant swirl of buying, selling and donating that marked the rhythms of daily life. It also maps the contact points between rulers and ruled, offering new insights on the motivations and actions of both peasant proprietors and aristocrats. Robert Portass is Senior Lecturer in Medieval History at the University of Lincoln.